2016
DOI: 10.5455/ijmsph.2016.100620157
|View full text |Cite
|
Sign up to set email alerts
|

Menstruation: a cross-sectional study on knowledge, belief, and practices among adolescent girls of junior colleges, Kuppam, Andhra Pradesh

Abstract: this period produce long-lasting effects for individual and public health and, in various ways, a nation's future lies in the strength and objectives of its youth population. [1] Nearly, in 500 BC, Sushruta Samhita noted that Indian girls commenced to menstruate at the age of 12 years. The importance of menstruation and menarche can be gauged by writing in Mahabharata that, "Each time an unwedded maiden has her monthly course, her parents or guardians are guilty of heinous crime of slaying the embryo." Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 5 publications
(23 reference statements)
6
17
0
Order By: Relevance
“…[29] The present study showed that 91.7% of female adolescents gave correct answers about the cause of menstruation as a normal sign of growth and puberty, while only 8.3% girls did not know the cause of menstruation. This finding is similar to the study results of Savanthe et al, who reported that most of the students (86%) understand that menstruation is normal phenomenon [28] and another finding by Das et al (2016) in a study conducted among high school girls in Vadodara city, wherein 70% identified that menstruation is a normal process. However, the findings of another study are consistent with the current results as it reported that 70% of the girls thought that menstruation is an unnatural process.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…[29] The present study showed that 91.7% of female adolescents gave correct answers about the cause of menstruation as a normal sign of growth and puberty, while only 8.3% girls did not know the cause of menstruation. This finding is similar to the study results of Savanthe et al, who reported that most of the students (86%) understand that menstruation is normal phenomenon [28] and another finding by Das et al (2016) in a study conducted among high school girls in Vadodara city, wherein 70% identified that menstruation is a normal process. However, the findings of another study are consistent with the current results as it reported that 70% of the girls thought that menstruation is an unnatural process.…”
Section: Discussionsupporting
confidence: 90%
“…[26,27] In the present study, the majority (88.3%) of the students females being menstruated between age of 11 to less than 15 years old, and about two-thirds had regular cycles, which coincide with the studies conducted in India by Savanthe et al (2016) and Kamath et al (2013). [14,28] In the same context, abdominal pain followed by back pain was found to be the most frequent complaint during menstruation among the students in the present study, which is similar to the results reported by Savanthe et al [27] Regarding knowledge about puberty and menstruation, the results of the current study revealed that more than half of the female adolescents had correct knowledge about the signs of sexual maturation in females such as breast development, pubic hair development, menstruation, increase in height and weight, which may be due to the information they achieved in courses on religion and biology. This is in line with a study conducted in Baghdad City, which reported that half of the adolescent girls had good awareness about pubertal changes (primary sex characteristics, attaining sexual maturity, onset of menstruation and pubic hair).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It is commonly associated with misconceptions, malpractices and health challenges among girls in developing countries (Bosch 2005;Benjet and Hernandez-Guzman 2001;Savanthe and Nanjundappa 2016). The physiological, mental and social effects of menarche are partly abrupt and partly start to influence a girl's health status gradually (Apter 1980).…”
Section: Level Of Maturationmentioning
confidence: 99%